Enhanced Stability and Bioavailability of Defatted Cricket Protein Hydrolysates Encapsulated in Alginate-Coated Liposomes - Chotphruethipong, Lalita; Benjakul, Soottawat; Aluko, Rotimi E.; Senphan, Theeraphol; Hutamekalin, Pilaiwanwadee; Sinthusamran, Sirima (My University, 2026)
The practical application of protein hydrolysates as functional food ingredients is frequently obstructed by their inherent structural instability. To circumvent this limitation, liposomal encapsulation has emerged as a sophisticated strategy to bolster the bioactivity and integrity of cricket-derived proteins. In this study, varying concentrations (1–4% w/v) of defatted cricket protein hydrolysate (DCPH) were integrated into vesicles composed of soy lecithin and cholesterol. The highest encapsulation efficiency (EE) was observed at a 2% DCPH loading capacity, yielding a significant result of 88.18% (p < 0.05). Subsequent coating with sodium alginate (SA) at 0.1–0.3% (w/v) resulted in an increase in particle size and a more pronounced negative surface charge. When maintained at 4 °C over a 24-day duration, the SA-coated liposome (SA-L-2%DCPH) exhibited superior stability compared to its uncoated (L-2%DCPH) counterpart. Also, the digest derived from the SA-L-2%DCPH exhibited significantly enhanced transepithelial permeability across the Caco-2 cell monolayer, indicated by the higher protein content and ABTS radical scavenging activity. Thus, sodium alginate-coated liposomes serve as a promising delivery system for encapsulating DCPH both during storage stability and in the gastrointestinal digestion system.
Keywords: alginate; bioavailability; coating; cricket; liposome; protein hydrolysate; stability